Analysis of the Effect of Revenue Growth, Cost Growth and Economic Value Added on the Financial Performance of Tritya Eye Clinic With Operation Cash Flow as an Intervening Variable - Sumirat, Esti; Ratnawati, Tri; Pristiana, Ulfi (International Journal of Economics (IJEC), 2024)
The purpose of this study was to analyze the effect of revenue growth, cost growth and economic value added on the financial performance of the Tritya Eye Clinic with operational cash flow as an intervening variable. This study uses a quantitative method with secondary data sources. The population of the study was all financial reports of the Tritya Eye Clinic for the period 2019 to 2023. The data analysis method used SEM-PLS analysis. The results of the study showed that partially the variables of revenue growth, cost growth and economic value added had no significant effect on Operation Cash Flow, the variables of revenue growth and cost growth had no significant effect on financial performance but the EVA variable had a significant effect on financial performance. While the variables of revenue growth, cost growth and economic value added had no significant effect on financial performance mediated by operational cash flow at the Tritya Eye Clinic in Surabaya